Questionnaire based study of drivers' error and violation at four-legged signalized intersection. Issue 9 (21st October 2022) - Sahu, Prasanta K.; Maji, Avijit; Nath, Bhargav; Roh, Hyuk-Jae
ABSTRACT: It is an enduring challenge to know the underlying determinants (factors and actors) for developing safe roads from the driving behavior perspective. Human (driver) errors and violations are generally referred as the most frequent cause of road accidents. This research analyzed a driver questionnaire survey of 584 drivers covering their behavior (error and deliberate violations) and safety-related attitudes while completing their driving task, at four-legged signalized intersections in India. We analyzed the driver behavior in terms of lane choice, signage and marking apprehension, tailgating, and vehicle speed consciousness at intersections, and their tendency to commit errors or violations. Driving frequency was found to have a significant effect on both Inattentive Error/Confused Error (IE/CE) and Risky Self-willed Violation (RSV). Gender was found to significantly affect only RSV and age influences only IE/CE. Highway agencies can consider the findings in developing user-friendly and self-explanatory road infrastructure with improved road users' safety features.